2014
DOI: 10.4236/jmmce.2014.24038
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of LDPE Reinforced with Calcium Carbonate—Fly Ash Hybrid Filler

Abstract: The synergetic effect of calcium carbonate (CC)-fly ash (FA) hybrid filler particles on the mechanical and physical properties of low density polyethylene (LDPE) has been investigated. Low density polyethylene is filled with varying weight percentages of FA and CC using melt casting. Composites are characterized for mechanical, thermal, microstructural and physical properties. Results show that the flexural strength increases with increases in FA content of the hybrid filler. It is evident from the study that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 29 publications
(38 reference statements)
1
12
0
3
Order By: Relevance
“…Since the surface property of the reinforced samples increased it shows resistance to the bending stress hence having higher flexural strength as compared to virgin LDPE. The same result was discussed by the author that the increase in Fly ash to polyethylene leads to increase in Flexural strength and modulus [4]. Gummadi et al also reported that flexural modulus increases for smaller filler loadings [6].…”
Section: Flexural Propertiessupporting
confidence: 67%
See 1 more Smart Citation
“…Since the surface property of the reinforced samples increased it shows resistance to the bending stress hence having higher flexural strength as compared to virgin LDPE. The same result was discussed by the author that the increase in Fly ash to polyethylene leads to increase in Flexural strength and modulus [4]. Gummadi et al also reported that flexural modulus increases for smaller filler loadings [6].…”
Section: Flexural Propertiessupporting
confidence: 67%
“…The 20wt % FA and 30wt% CC with higher density of (1.78 g/cm 3 ) is found to be the optimum combination. An increase of 7.27% in micro-hardness over virgin polyethylene is obtained in composites with 10 wt% FA and 40 wt% CC [4].…”
Section: Introductionmentioning
confidence: 96%
“…It is reported in the literature that CC or RHA individually provides positive effect, but in combination, they do not support each other and such behavior is observed. This may be attributed to multiple filler loading causing more fracture sites 45 . The stress-strain curves for PP and PP composites are shown in Figure 4 along with the shape and color of dog bone samples.…”
Section: Mechanical Testingmentioning
confidence: 99%
“…There are many references in the literature studying the mechanical properties of plastics filled with calcium carbonate (Adeosun and Usman, 2014;Eiras and Pessan, 2009;Roussel et al, 2005). In their study, Roussel et al,(2005) say that it is possible to improve productivity in the process through the use of calcium carbonate because of its thermal conductivity, specific heat and thermal expansion characteristics.…”
Section: Calcium Carbonate Filled Plastics Vs Virgin Plasticsmentioning
confidence: 99%